Protective effect of lycopene on adriamycin-induced cardiotoxicity and nephrotoxicity - Yilmaz, S; Atessahin, A; Sahna, E; Karahan, I; Ozer, S (Elsevier Ireland Ltd, 2006)
The aim of this study was to investigate the possible protective role of lycopene on adriamycin (ADR)-induced heart and kidney toxicity using biochemical and histopathological approaches. Rats were randomly divided into four groups. The first group received no medication and was regarded as the control group; the second group was injected with a single dose of ADR; the third group was treated with lycopene for 10 days before ADR injection and the last group was treated with lycopene for 2 days before and for 3 days after the administration of a single dose of ADR. ADR (10 mg/kg) was intraperitoneally (i.p.) injected as a single dose and lycopene (4 mg/kg) was administered in corn oil by gavage. The levels of malondialdehyde (MDA) and reduced glutathione (GSH) in both the heart and kidneys were higher in the group treated with ADR alone than in the control group, and were lower in the groups administered with lycopene than in the ADR alone group. Although the activity of catalase (CAT) in the heart was higher in the ADR alone group than in the control group, it was lower in the kidneys. In particular, treatment with lycopene post-injection normalized both cardiac and kidney CAT activities. In heart and kidney tissues, glutathione peroxidase (GSH-Px) activities were not significantly different between all groups. Significant increases in the levels of plasma creatinine and urea were observed in the ADR group when compared to the control group, and these increases were normalized by lycopene treatment. Cardiac and renal histopathological changes were observed in the ADR group as compared to the control group. In contrast, these histopathological changes appeared nearly normal in the groups treated with lycopene pre- and post-injection. In conclusion, this study clearly indicated that ADR treatment markedly impaired cardiac and renal function and that treatment with lycopene might prevent this toxicity in rats. (C) 2005 Published by Elsevier Ireland Ltd.
Keywords: doxorubicin; lycopene; heart; kidney; lipid peroxidation; antioxidants; histopathology